Evaluation of in vitro and invivo anti-inflammatory activities of Parthenium camphora - Gupta, Vinay; Chauhan, Shefali; Prakash, Archana; Mathur, Abhishek (Recent Research in Science and Technology, 2013)
The present investigation was carried out to evaluate the anti-inflammatory potential of solvent extracts of Parthenium camphora (Family: Compositae), a non-useful and waste weed growing through waste sides. The anti-inflammatory activities were assessed through in vitro and in vivo procedures, the results were found to be very surprising and promising. Aqueous and Ethanolic solvent extracts of Parthenium camphora were found to have significant anti-inflammatory activity at doses 100 and 120 mg/Kg during in vitro anti-inflammatory assay. The ethanolic fractions of the plant causes significant reduction in inflammation i.e. 92 % (120 mg/kg) followed by aqueous extract i.e. 85 % (120 mg/kg) compared to standard anti-inflammatory drug, Diclofenac Sodium i.e. 87 % (10 mg/kg). The values of reduction in paw volume, 0.10 ± 0.05, 0.14 ± 0.05 and 0.16 ± 0.05 were found significantly of ethanol extract, aqueous extract and Diclofenac sodium, respectively at 4 h after carrageenan administration. Ethanolic extracts showed potent anti-inflammatory activity in comparison to aqueous extracts. The extracts showed higher anti-inflammatory potential as the dose varies. Thus results showed that extracts showed significant anti-inflammatory activity in dose-dependent manner. The extracts exhibited membrane stabilization effect by inhibiting hypotonicity induced lysis of erythrocyte membrane. The erythrocyte membrane is analogous to the lysosomal membrane, and its stabilization implies that the extract may as well stabilize lysosomal membrane. Stabilization of lysosomal membrane is important in limiting the inflammatory response by preventing the release of lysosomal constituents of activated neutrophils such as bacterial enzymes and proteases which cause further tissue inflammation and damage. From the above study it was concluded that the ethanolic extract of Parthenium camphora has significant membrane stabilization property compared to the aqueous extract of the same plant and it was comparable to the standard drug Diclofenac Sodium.